Unusual presentation of mesenteric cyst in a 3-year-old child - A case report (Indian Journal of Case Reports, 2018)
Mesenteric lymphatic cysts are rare congenital benign malformations of the lymphatic system. Rarely, the wall of the lymphatic cyst can undergo calcification mimicking other conditions. In the literature, about six cases of calcified lymphatic cyst have been reported. Here, we present the case of a 3-year-old child who presented with vague abdominal pain and diagnosed to have an intra-abdominal calcified cyst. On exploration, the cyst was arising from the mesentery and the child required excision of the cyst with the involved intestine. The biopsy was suggestive of a mesenteric lymphatic cyst.